Does the legal environment matter for financial inclusion? Evidence from panel data econometric analysis - Mourad, Guettaf Kherkhachi; Slimane, Zouari Ferhat (The International tax journal, 2026)
This study examines the role of the legal environment in promoting financial inclusion by integrating legal quality indicators into an applied econometric analysis. The main purpose of the research is to assess whether improvements in the legal environment contribute significantly to expanding access to and usage of formal financial services. Using panel data covering a group of developing economies over a multi-year period, the study employs advanced panel data estimation techniques to control for unobserved heterogeneity and ensure robust results. Financial inclusion is measured through indicators related to account ownership, access to banking services, and credit availability, while the legal environment is captured through proxies reflecting rule of law, regulatory quality, and contract enforcement. The empirical findings indicate that a stronger legal environment has a positive and statistically significant effect on financial inclusion, even after controlling for macroeconomic and institutional factors. The results highlight the importance of legal and regulatory reforms as a complementary policy tool for enhancing financial inclusion. This study adds value by providing empirical evidence on the legal–financial inclusion nexus and offers practical insights for policymakers seeking inclusive and sustainable financial development.